2017
DOI: 10.1136/jmedgenet-2016-104346
|View full text |Cite
|
Sign up to set email alerts
|

Novel and known ribosomal causes of Diamond-Blackfan anaemia identified through comprehensive genomic characterisation

Abstract: Overall, heterozygous pathogenic variants in ribosomal genes were identified in 44 of the 61 families (72%). De novo pathogenic variants were observed in 57% of patients with DBA. Ongoing studies of DBA genomics will be important to understand this complex disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 27 publications
(15 reference statements)
1
55
0
1
Order By: Relevance
“…These data demonstrate that TSR2, which is biochemically unlinked from the mature ribosome and which has a key role in the production of adequate ribosome levels, is necessary for in vivo erythroid lineage commitment from human HSPCs. Considering these findings from a rare experiment of nature in addition to the more frequent RP mutations in DBA (Mirabello et al, 2017), we hypothesized that ribosome levels may have a selective role in human hematopoietic lineage commitment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrate that TSR2, which is biochemically unlinked from the mature ribosome and which has a key role in the production of adequate ribosome levels, is necessary for in vivo erythroid lineage commitment from human HSPCs. Considering these findings from a rare experiment of nature in addition to the more frequent RP mutations in DBA (Mirabello et al, 2017), we hypothesized that ribosome levels may have a selective role in human hematopoietic lineage commitment.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have shown that the defect present in DBA appears to occur in early progenitors that are quantitatively reduced, but the few cells that do persist undergo normal terminal maturation (Nathan et al, 1978; Ohene-Abuakwa et al, 2005). The majority of DBA cases are caused by heterozygous loss-of-function mutations in one of 18 different ribosomal protein (RP) genes, resulting in RP haploinsufficiency (Mirabello et al, 2017). Despite extensive studies, the mechanisms by which a defect in RPs could cause a selective absence of erythroid cells within the hematopoietic compartment, while allowing for normal differentiation of other lineages, has remained a mystery (Sankaran and Weiss, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DBA is usually caused by heterozygous mutations in ribosomal protein (RP) genes that lead to haploinsufficiency. To date, mutations in 19 RP genes ( RPS19, RPS24, RPS17, RPL35A, RPL5, RPL11, RPS7, RPS10, RPS26, RPL26, RPL15, RPL31, RPS29, RPS28, RPL27, RPS27, RPS15A, RPL35, RPL18 ) have been identified in DBA patients (Cmejla, Cmejlova, Handrkova, Petrak, & Pospisilova, ; Doherty et al., ; Draptchinskaia et al., ; Farrar et al., , ; Gazda et al., , , ; Gripp et al., ; Ikeda et al., ; Landowski et al., ; Mirabello et al., , ; Wang et al., ). Rare mutations in GATA1 , that abrogate the production of the full‐length protein (Parrella et al., ; Sankaran et al., ), and in TSR2 , encoding a RPS26 interactor (Gripp et al., ), have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…13 The widely accepted pathophysiology of DBA is that ribosomal protein mutations render erythroid progenitor cells profoundly sensitive to apoptosis, ultimately leading to failure of the erythropoietic lineage development. 14 8,[15][16][17][18][19][20][21][22] This results in ribosomal stress and subsequent activation of the p53 tumor suppressor pathway, which is perceived as the primary origin for the clinical manifestations. 23 The exact mechanism for the isolated red cell aplasia has not been established yet.…”
Section: Introductionmentioning
confidence: 99%